Integration of Education and Research into Healthcare Services According to Health Upstream Documents in the Islamic Republic of Iran - Seyed Jamaleddin Sajadi -Jazi (Strides in Development of Medical Education)
Background: This paper provides an overview of the plan of integration of education and research into healthcare services, as outlined in upstream laws and documents. Legal documents serve as a guiding framework for the direction of a nation’s health system. The desired vision for the health system is typically reflected in development policies and plans. Having up-to-date health national policies is viewed as a hallmark of good governance in health systems. Fortunately, this issue has been given due attention in our country.Objectives: This paper provides an overview of the plan of integration of education and research into healthcare services, as outlined in upstream laws and documents.Methods: A library-based study method (reviewing reputable domestic and international publications on the keywords related to the study) was used to review upstream laws and documents related to the general health policies and content analysis.Results: The emphasis on the inherent importance and necessity of integration of education and research into healthcare services, as well as the mission to fulfill it, has been clearly articulated in upstream laws and documents in the health sector, at specific time intervals and in accordance with societal needs.Conclusion: The integration of education and research into healthcare services has been a revolutionary and highly beneficial achievement for our country. Thus, given our country’s health system state, the promulgated upstream laws and documents have comprehensively addressed all necessary aspects for strengthening the national health system, and can play a significant role in transforming the health system and advancing its objectives.